Hernández, Antonio María; Barrera Buteler, Guillermo (Coords.), Derecho Público Provincial, 3ª edición, Buenos Aires, Abeledo-Perrot, 2020, 944 pp - Ábalos, María Gabriela (2020)
Fil: Ábalos, María Gabriela. Universidad Nacional de Cuyo; Argentina